IMPLEMENTATION OF CERTAINTY FACTOR METHOD TO IDENTIFY GASTROESOPHAGEAL REFLUX DISEASE (GERD) AT PUSKESMAS SIDODADI - Fadly Annazilli; Hambali Hambali; Suparmadi Suparmadi (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2023)
The Expert System is one part of artificial intelligence which is designed to mimic the expertise of an expert in answering questions and solving problems in the fields of health, medicine, business, economics and so on. Certainty factor is thought of when using an inference engine (decision-making machine) and can be logically described as a repetition application of the ponens mode (a set of inference rules and valid arguments) Gestroesophageal Reflux Disease (GERD) is a type of disease that is often experienced by the community, and this type of disease is the disease that has the most number of patients in the Sidodadi Health Center because there are still many people who pay less attention to the disorders and the causes and symptoms that occur in gastric diseases. By utilizing an expert system to identify diseases in the stomach that are devoted to detecting Gastroesophageal Reflux Disease (GERD) at the Sidodadi Health Center through symptoms or complaints experienced by the community, the result is that the level of confidence from the results of diagnosis using the certainty factor method is 81%.